A new species of Paretroplus (Teleostei: Cichlidae: Etroplinae) from northeastern Madagascar, with a phylogeny and revised diagnosis for the P. damii clade - Sparks, John S.; Schelly, Robert C. (Zootaxa, 2011)
Paretroplus loisellei, a new species of etropline cichlid from Madagascar, is described from the middle to lower reaches of the Mahanara River, located to the north of the Masoala Peninsula in northeastern Madagascar. The new species is recovered within the “Paretroplus damii clade” on the basis of several apomorphic anatomical features, including the presence of a triangular, black or dark gray, pectoral-axil patch, chest scales that are greatly reduced in size and highly embedded, and flank scales in which the posterior field is thin and unossified. The new species is distinguished from its sister taxon, P. damii, by a more or less horizontal profile extending from the anterior margin of the lower jaw to the ventroposterior margin of the suspensorium (vs. strongly rounded and convex), horizontally oriented oral jaws with fleshy lips (vs. oblique and thin), tricuspid symphyseal teeth in the upper jaw with distinct and sharp lateral cusps, a much darker overall pigmentation pattern, and distinctive bright golden breeding coloration (vs. brick red).